Relationship between Total Flight Hours and Individual Factors with Low Back Pain in Indonesian Military Helicopter Pilots - Fazlin Khuzaima; Retno Wibawanti; Agus Sugiharto; Wawan Mulyawan; M. Ilyas; Dewi S. Soemarko (The Indonesian Journal of Community and Occupational Medicine, 2023)
Introduction: Helicopter pilots are potentially at risk of Low Back Pain (LBP) and are twice as likely as fighter pilots to experience it. Helicopter pilots’ LBP is caused by a combination of risk factors: engine and rotor vibration, ergonomic risks due to cockpit design, static seating position due to operations, and individual factors. These factors are incorporated into cumulative aviation risk exposure, which can be measured by total flight hours. The prevalence of LBP in Caucasians is high, at 50.5%-92%. However, there has not been any research on Indonesian military helicopter pilots who have a different posture from Caucasians.Objective: To determine the prevalence of LBP, to analyze the relationship between total flight hours and individual factors (age, height, BMI, exercise habits, and smoking habits) with LBP in Indonesian military helicopter pilots.Methods: The study was conducted at the Indonesian Army and Indonesian Air Force with total sampling method as many as 124 people. An explanation was carried out followed by filling in the consent to become a research subject, filling in personal data, anamnesis, Numeric Rating Scale (NRS), physical examination, neurological examination, and total flight hour data.Results: There were 124 subjects, consisting of 37.9% pilots and 62.1% copilots, 87.9% of pilots operate large helicopters, have average total flight hours of 450 hours, age of 30 years, the height of 172.66 cm, low intensity exercise habits of 61.3%, and smokers as much as 45.2%. A total of 57 people (46%) experienced LBP. Statistical results showed that total flight hours had an association with LBP (p = 0.035) where each 1 unit increase in total flight hours had a 1.02 times greater chance of LBP.Conclusion: The prevalence of LBP is 46% and there is an association between total flying hours and LBP in Indonesian military helicopter pilots.